2020
DOI: 10.2174/1573399816666200211120402
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Review on Nutritional Requirements and Assessment for Type 2 Diabetes Mellitus with Chronic Renal Disease

Abstract: Background: A significant correlation exists between type 2 diabetes mellitus (T2DM) and chronic kidney disease (CKD), where up to 40% of diabetic patients suffer from CKD as a direct result of diabetic complications. Management of diabetes in CKD patients can be challenging due to their need for disease-specific diets, as well as increased risks of complications due to malnutrition, which is why their dietary needs and nutritional requirements necessitate attention to detail, and have to be assessed and tail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Furthermore, a systematic review and meta-analysis of 37 unique epidemiological studies comprising 348,259 participants support that elements including As, Pb, Cd, and Cu are associated with the increased risks of cardiovascular disease and coronary heart disease ( 49 ). Malnutrition intervention has been reported to improve these chronic disease statuses ( 50 , 51 ). In combination with these results, it was suggested that elevated essential and non-essential elements levels may increase the potential risk of cardiovascular disease in the elderly by promoting malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a systematic review and meta-analysis of 37 unique epidemiological studies comprising 348,259 participants support that elements including As, Pb, Cd, and Cu are associated with the increased risks of cardiovascular disease and coronary heart disease ( 49 ). Malnutrition intervention has been reported to improve these chronic disease statuses ( 50 , 51 ). In combination with these results, it was suggested that elevated essential and non-essential elements levels may increase the potential risk of cardiovascular disease in the elderly by promoting malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, diabetes, diabetic nephropathy, diabetic kidney disease (DKD), chronic kidney disease (CKD), and atherosclerotic cardiovascular disease (ASCVD) have been prevalent worldwide [1]. Among them, a protein-restricted diet has been often used for patients with impaired renal function.…”
Section: Abbreviationsmentioning
confidence: 99%
“…On the other hand, recent reports showed controversial results that the C-peptide levels are increased in the ESRD patients 3 . Oher factors such as deterioration in nutritional status, changes due to diabetes medications 6 and reduced gluconeogenesis in the renal failure have been suggested 7 . Furthermore, decline in kidney function is also thought to induce insulin resistance 8 .…”
Section: Introductionmentioning
confidence: 99%